The First Decade of Web-Based Sports Injury Surveillance: Descriptive Epidemiology of Injuries in US High School Girls' Basketball (2005-2006 Through 2013-2014) and National Collegiate Athletic Association Women's Basketball (2004-2005 Through 2013-2014) - Clifton, D. R.; Hertel, J.; Onate, J. A.; Currie, D. W.; Pierpoint, L. A.; Wasserman, E. B.; Knowles, S. B.; Dompier, T. P.; Comstock, R. D.; Marshall, S. W.; Kerr, Z. Y. (Journal of Athletic Training, 2018)
Context The advent of Web-based sports injury surveillance via programs such as the High School Reporting Information Online system and the National Collegiate Athletic Association Injury Surveillance Program has aided the acquisition of girls' and women's basketball injury data.